THEORETICAL APPROACHES TO THE DEFINITION OF “LAND TRANSFER” AND “LAND PLOT TRANSFERABILITY” IN THE RUSSIAN LAND AND CIVIL LAW - P. Rumyantsev, Fedor (Gênero & Direito, 2020)
the relevance of the problem under study is due to the fact that scientific concepts do not offer a shared vision of the essence of transferability and types of agricultural land plot transfer. Analysis of the problems arising in this sphere provided herein is of major importance to land and civil law. The article is aimed at formulating a theoretical definition of land transfer, which may apply to land plots of any categories not withdrawn from transfer, including transfer of agricultural land plots. The leading approach to the study of the problem at hand is the logical method of system analysis, which allows to educe peculiarities of agricultural land transfer conditioned by specific features of a transferable item. The research article yields the following main results: it uses the data of comprehensive study of the law and specialist scholarly literature to identify the peculiarities of both public and private agricultural land plot transfer and offers the author’s definition of transfer. The article provides arguments for the recognition of public (administrative) transfer as a variety of land transfer. The article justifies the need to specify general principles of determining transferability of land plots of any category, including land plots from agricultural land, in the Russian Land Code. Article materials may be of use when developing the land law theory, expanding the theory of agricultural land transfer regulation, in the elaboration of some fundamental definitions and scientific classifications and in the theoretical justification of lines of improvement of the land transfer law. The theoretical suggestions provided may be used when teaching land law, individual sections in the civil law course and when preparing textbooks, teaching aids and study guides.